Factors affecting quality of life of fracture patients with productive age at dr. Haryoto Regional General Hospital, Lumajang District, East Java - Yugiana, Anastasya Marli; Martini, Santi (Universitas Udayana, 2021)
Background and purpose: Fractures can affect activity and productivity due to delayed time of returning to work. It may have impacts on the patient’s physical, psychological, social, and environmental conditions that can influence the quality of life. The purpose of this study was to explore factors associated with the quality of life of fracture patients with productive age. Methods: This research used a cross sectional approach conducted at the Orthopedic Clinic of dr. Haryoto Regional General Hospital, in Lumajang District, East Java from October 2020 to February 2021. The study involved 84 patients whom were selected using simple random sampling. Data was collected with interview using the WHOQOL-BREF questionnaire which can assess a person’s quality of life. The data were analysed using univariable, bivariable and multivariable analysis with Chi-square and Logistic Regression. Results: Most respondents were aged 20 to 60 years, male, have worked, completed secondary education, and married. Most of them had health insurance, experienced fractures in lower extremity with open fracture type, had severe condition since more than 12 months and had an accident on the highway. Factors associated with quality of life were family support with OR=0.631 [95%CI: 0.524-0.760; p=0.004], duration of fracture with OR=0.333 [95%CI: 0.123–0.900; p=0.049] and fracture severity with OR=11.00 [95%CI: 3.261–37.106; p=0.00]. Conclusion: Family support, duration of fracture, and fracture severity were associated with quality of life of productive aged fracture patients. Special attention and family support are needed for fracture patients during the healing period to improve their health status.